Implementasi Media Video Pembelajaran pada Materi Gangguan Sistem Gerak dan Cara Mencegahnya - Zega, Victor Hepi Destalenta; Zega, Yatatema; Lase, Natalia Kristiani (Indo-MathEdu Intellectuals Journal, 2024)
Biology learning about the system of motion in humans relies heavily on the use of learning media. Technological advances in the modern era have provided significant support for various learning resources, with the aim of increasing affordability for students in the learning process. As a result, educators try to inspire students' motivation towards the material to be learned. This study aims to determine the use or implementation of learning video media for disorders or symptoms in the motor system and how to overcome these disorders. The method used in this article is a literature study, which involves collecting data by understanding and researching theories from various literature relevant to the research. The data analysis technique used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results of this study are responses from teachers and students showing that learning media in the form of encyclopedias is very practical. The practicality of this media is especially evident in its use during the learning process. Teachers and students can access learning videos without the need to install additional apps on laptops. This media can be accessed in various places and times and includes learning links that support students' better understanding of motion system materials.